Residential Instability and Suicidal Ideation Among Persons on Parole - Boyas, Javier F. (International journal of offender therapy and comparative criminology, 2023)
Parolees experience numerous barriers that may impact successful reintegration into society. Residential instability may further add to these obstacles, as there may be limited opportunities for housing given their criminal history. The present study aimed to examine the impact of residential instability on suicidal ideation among parolees. Results indicated that residentially stable and unstable individuals had similar risk factors which were significantly associated with suicidality, such as age and having perceived unmet mental health needs. Other risk factors differed among the two groups, highlighting the importance of treatment and preparation for re-entry into society while in the prison setting.